CHANGES IN THERMALLY STIMULATED CONDUCTIVITY OF CsPbBr3 AND CsPbCl3 CRYSTALS EXPOSED TO X-RAY IRRADIATION - Bohdan Pavlyk; Roman Lys; Roman Gamernyk; Mykola Goydalo (Електроніка та інформаційні технології)
Introduction. CsPbBr3 and CsPbCl3 crystals remain among the most intensively studied materials. This is due to their high efficiency in solar cells, which currently exceeds 22%. However, an unsolved problem is the degradation of these perovskites under the influence of external factors.